The Southeastern Librarian, Vol.39, No.04, Winter 1989 - Curry, Elizabeth; Calhoun, Katharine (The Southeastern Library Association, 1989)
The Southeastern Librarian, Vol.39, No.04, Winter 1989. Periodical.
1 electronic record. 46 pages. Scanned from original document. Contents Include: SELA Officers and Staff 1988-90 - cover verso, State Library Association Officers - cover recto, President’s Page - 132, Editor’s Musings - 133. ARTICLES: External User Access to Academic Libraries by Ralph Russell, Carolyn L. Robison, and James E. Prather - 135-138, Librarians in Academic Limbo: Support for Scholarship by Donald J. Kenney, Gail McMillan - 139-141, To Market, To Market: Academic Reference Departments and the Promotion of CD-ROMS by Carmen Embry and Glenda Neely - 143-144, Counting Down to the Second White House Conference: The Role of WHCLIST by Charles E. Beard - 161. DEPARTMENTS: Bulletin Board - 146, Calendar - 170, Keeping Up - 159, Looking Back - 134, New & Useful - 154, People - 156, Stateside View - 149. SELA ASSOCIATION NEWS: Financial Report - 168, Guidelines for SELn Submissions - 134, Membership Form - 169, Nominating Committee Report - 162, New Members - 163, Award Forms - 166-167.
Keywords: Periodicals | Southeastern Library Association